Traditional Art-Making and Emerging Technologies: An Individual Journey into AI and AR Integration in Portrait Creation - Mossalim, Jihane (The Canadian Art Teacher / Enseigner les arts au Canada)

(untitled) (Canadian Society for Education through Art / Société canadienne d’éducation par l’art, 2023)
In this article, I share my personal process and outcomes while merging traditional art-making methods with emerging technologies to create portraits. Through the creation of eight oil portrait paintings with AI and AR components, I explore questions and meanings surrounding the combination of artificial intelligence (AI) and augmented reality (AR) with conventional art-making tools. I also investigate how emerging technologies, such as AI and AR, can complement traditional artistic approaches like painting and drawing. By conducting interviews, maintaining a journal, and creating the portraits, I delve into the subject, uncovering many contrasts between traditional media and emerging technologies, both in terms of physical and mental aspects. I describe how this combination of media significantly impacted my creative process and the final artworks' outcomes. In conclusion, I contemplate the broader implications of integrating emerging technologies into art classes, and how elementary teachers can utilize and teach these innovations as tools for creating art. This study opens up new possibilities for artistic expression, reflecting on the potential of blending tradition and technology in the realm of art-making.